2009
DOI: 10.1039/b809588d
|View full text |Cite
|
Sign up to set email alerts
|

Field comparison of passive air samplers with reference monitors for ambient volatile organic compounds and nitrogen dioxide under week-long integrals

Abstract: This study evaluates performance of nitrogen dioxide (NO2) and volatile organic compound (VOC) passive samplers with corresponding reference monitors at two sites in the Detroit, Michigan area during the summer of 2005. Ogawa passive NO2 samplers and custom-made, re-useable Perkin-Elmer (PE) tubes with Carbopack X sorbent for VOCs were deployed under week-long sampling periods for six weeks. Precise results (5% relative standard deviation, RSD) were found for NO2 measurements from collocated Ogawa samplers. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
2
22
1
Order By: Relevance
“…The precision of duplicate samples was <10%, with the exception of styrene, which had low concentrations. This is comparable to similar precision estimates found in earlier studies using the same passive sampler in Detroit (Mukerjee et al, 2009) and Dallas (Smith et al, 2011); similar precision was estimated for benzene in Corpus Christi (Thoma et al, 2011). Table 2 reports the outcome of pairwise tests and Hodges-Lehmann estimates of the differences.…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…The precision of duplicate samples was <10%, with the exception of styrene, which had low concentrations. This is comparable to similar precision estimates found in earlier studies using the same passive sampler in Detroit (Mukerjee et al, 2009) and Dallas (Smith et al, 2011); similar precision was estimated for benzene in Corpus Christi (Thoma et al, 2011). Table 2 reports the outcome of pairwise tests and Hodges-Lehmann estimates of the differences.…”
Section: Methodssupporting
confidence: 71%
“…This yearlong study reported that these samplers were comparable to reference VOC methods (Thoma et al, 2011). Similar comparison results with these samplers have been found elsewhere (McClenny et al, 2006;Mukerjee et al, 2009;Smith et al, 2011). The Corpus Christi study also reported elevated benzene concentrations downwind of the refinery and demonstrated the effectiveness of using this sampler for fenceline monitoring.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Passive samplers were reuseable PerkinElmer style tubes containing Carbopack X sorbent (Supelco FLM Carbopack X Deactivated Stainless Steel TD Tubes, 89 mm, part number 28686-U, Sigma-Aldrich Co. LLC, St. Louis, MO) deployed for 14-day sampling periods. The passive sampler has been evaluated in lab and field studies and is comparable to standard methods for VOCs (McClenny et al, 2005;2006;Mukerjee et al, 2009;Smith et al, 2011;Thoma et al, 2011Thoma et al, , 2015. Duplicate sampling was conducted for all sampling periods to evaluate precision, and quality control (QC) samples consisting of field blanks and field spikes were also prepared for all sampling periods to allow evaluation of tube background contributions and recoveries of target compounds from the Carbopack X sorbent tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Specific procedures have been reported (Williams et al, 2009). These devices have been used extensively in other EPA studies and details of their use and validation were reported earlier (Williams et al, 2003;Mukerjee et al, 2004Mukerjee et al, , 2009.…”
Section: Environmental Monitoringmentioning
confidence: 99%